Study of Few Layer Graphene Synthesised by Interlayer Catalytic Exfoliation Method - Chen, Tong Yang (2019)
Graphite is formed by weak Van der Waals force that connecting two-dimensional graphene layers together and strong covalent bond that forms between the adjacent planes of the carbon atoms that create small carbon to carbon distance. Graphene sheet is an atomic layer of graphite and it is formed by carbon atoms that are arranged in a simple honeycomb or hexagonal lattice. Graphite intercalated compound (GIC), fewlayer graphene (FLG) and graphene are the promising materials to improve the storage capacity of capacitor. Even though graphene has the highest energy storage capacity, however, the synthesis cost of graphene is high. In this project, GIC and FLG will be used as the materials to fabricate supercapacitor. The performance of a normal capacitor will be used to compare with the capacitor that is fabricated by using GIC and FLG. The method that was utilised in this project to synthesis FLG was interlayer catalytic exfoliation. Iron (III) chloride graphite intercalated compound (FeCl3 − GIC) can be obtained by intercalating iron (III) chloride (FeCl3) into the layered structure of graphite. In order to obtain iron (III) chloride few-layer graphene (FeCl3 − FLG), FeCl3 − GIC had to be ultrasonicated for 3 hours. Next, the synthesised FeCl3 − GIC and FeCl3 − FLG will then characterise by SEM, FESEM, EDX, XRD and FTIR to validate the results. SEM results of FeCl3 − GIC shows that there were FeCl3 intercalated into the layered structure of graphite and hence formed FeCI3 − GIC. Whereas, the SEM and FESEM of FeCl3 − FLG show that it is formed by the combination of two to five layers of graphene sheets. The results of EDX and XRD supported the results of SEM and FESEM by proving that there were traces of FeCl3 found in both FeCl3 − GIC and FeCl3 − FLG samples. Moreover, FTIR results of FeCl3 − GIC and FeCl3 − FLG eliminated the possibility of the formation of graphene oxide (GO). The synthesised FeCl3 − GIC and FeCl3 − FLG were then used as the materials to fabricate supercapacitor. By comparing the performance of normal capacitor and supercapacitors, the results show that FeCl3 − GIC supercapacitor was able to store about 30 times more energy than a normal capacitor, whereas FeCl3 − FLG supercapacitor is able to store about 70 times more energy than a normal capacitor. FeCl3 − GIC and FeCl3 − FLG had showed an excellent results on energy storage system, it is definitely a missing puzzle for taking current technology to the next level.